A modified lithium-rich manganese-based lithium-ion battery positive electrode material and preparation method

By setting the conductive layer and cladding layer on the surface of the positive electrode material of the lithium-rich manganese-based lithium-ion battery, the problem of capacity attenuation of the positive electrode material during the cyclic charge and discharge process is solved, and the electrochemical performance and cyclic endurance are improved.

CN119029199BActive Publication Date: 2025-02-07QINGDAO DUOYUAN LITHIUM IND CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411495525.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-07
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

The positive electrode material of lithium-rich manganese-based lithium-ion battery has obvious capacity attenuation problems during the cycle charging and discharging process, resulting in a significant reduction in commercial endurance.

Method used

Li1.2Ni0.13Co0.13Mn0.54O2 positive electrode particles are used, and a conductive layer and a cladding layer are arranged in sequence from the inside to the outside of the surface. The conductive layer is Li0.33La0.557Ti0.7Cr0.3O3, and the cladding layer is made of aluminum oxide. and gallium oxide composite material.

Benefits of technology

The provided cladding layer provides an inert protective film layer to alleviate the capacity attenuation caused by electrolyte corrosion and increased interface resistance. The conductive layer improves the conduction capacity of lithium ions and electrons, improves the overall electrochemical performance, and extends the cycle endurance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029199B_ABST
    Figure CN119029199B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified lithium-rich manganese-based lithium ion battery positive electrode material and a preparation method thereof, comprising a chemical formula of Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The positive electrode particles of O2 have a conductive layer and a coating layer on the surface of the positive electrode particles from the inside to the outside. The conductive layer is made of Li 0.33 La 0.557 Ti 0.7 Cr 0.3 O3; the coating layer adopts a composite material of aluminum oxide and gallium oxide; the modified lithium-rich manganese-based lithium-ion battery positive electrode material and preparation method can provide an inert protective film layer for the positive electrode material through the provided coating layer, and can slow down the capacity decay problem caused by electrolyte corrosion and increased interface resistance during the charge and discharge cycle; the conductive layer provides a conductor structure, which can improve the conductivity of lithium ions and electrons, improve its first cycle specific capacity, and obtain better electrochemical performance as a whole; the conductive layer and the coating layer cooperate with each other, which can slow down the capacity decay loss, while improving its specific capacity, so that its cycle endurance is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion battery positive electrode materials, and in particular to a modified lithium-rich manganese-based lithium ion battery positive electrode material and a preparation method thereof. Background Art

[0002] Lithium-ion batteries are widely used in electronic products, electric vehicles and other fields. With the development of the new energy industry, the performance requirements of lithium-ion batteries are increasing, and the positive electrode material is the key to improving the performance of lithium-ion batteries.

[0003] Lithium-rich manganese-based positive electrode materials are a type of lithium-ion battery positive electrode material with great potential. Their specific capacity is good and can reach more than 200mAh / g. However, they have been found to have obvious capacity decay problems during the cyclic charge and discharge process, which greatly reduces their commercial endurance. Therefore, it is necessary to consider how to further improve the stability of the material during the charge and discharge cycle and slow down the capacity loss. In view of this, we propose a modified lithium-rich manganese-based lithium-ion battery positive electrode material and a preparation method. Summary of the invention

[0004] The purpose of the present invention is to solve the deficiencies mentioned in the above background technology and provide a modified lithium-rich manganese-based lithium-ion battery positive electrode material and a preparation method thereof.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A modified lithium-rich manganese-based lithium-ion battery positive electrode material, comprising a chemical formula specifically Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles, wherein the surface of the positive electrode particles is provided with a conductive layer and a coating layer in sequence from the inside to the outside;

[0007] The conductive layer uses Li 0.33 La 0.557 Ti 0.7 Cr 0.3 O3;

[0008] The coating layer is made of a composite material of aluminum oxide and gallium oxide.

[0009] Preferably, the coating amount of the conductive layer accounts for 1-2% of the mass of the positive electrode particles.

[0010] Preferably, the coating amount of the coating layer accounts for 0.5-1% of the mass of the positive electrode particles.

[0011] Preferably, the conductive layer raw materials are chromium sulfate hexahydrate, lanthanum nitrate hexahydrate, titanium sulfate and lithium hydroxide.

[0012] Preferably, the raw materials of the aluminum oxide and gallium oxide composite material include aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio of 1:0.2-1.

[0013] A method for preparing a modified lithium-rich manganese-based lithium-ion battery positive electrode material, the specific steps of the method for preparing the positive electrode material are:

[0014] Step 1: Preparation of Li by sol-gel method 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles are reserved;

[0015] Step 2: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 cathode particles are mixed into deionized water to obtain a suspension;

[0016] Step 3: dissolving chromium sulfate hexahydrate, lanthanum nitrate hexahydrate and titanium sulfate in deionized water to obtain a solution, mixing the solution with the suspension, adding lithium hydroxide, stirring for 5-30 minutes and then filtering and drying;

[0017] Step 4: 600-700°C, keep warm for 4-6 hours, and sieve out the positive electrode particles coated with the conductive layer with a particle size less than 0.5 μm;

[0018] Step 5: Mix aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio, add to anhydrous ethanol and ultrasonically treat for 0.5-1h, add the positive electrode particles coated with the conductive layer in step 4, and stir at room temperature for 1-2h;

[0019] Step 6: Heat and stir in a water bath at 60-80°C until the anhydrous ethanol is evaporated to dryness, and then put it into a muffle furnace and calcine at 500-600°C for 5-6h to obtain positive electrode particles coated with aluminum oxide and gallium oxide.

[0020] Preferably, the sol-gel method comprises the following specific steps:

[0021] Step 1: Weigh 1.75 parts of LiNO3, 0.77 parts of Ni(NO3)2·6H2O, 0.77 parts of Co(NO3)2·6H2O, 2.67 parts of Mn(CHCOO)2·4H2O, 10.34 parts of citric acid monohydrate, and 1 part of polyvinylpyrrolidone, respectively, by mass, and mix to obtain one unit of raw material component. Each unit of raw material component is dissolved in 25 ml of ethylene glycol, and stirred at 70-85°C for 8-12 hours to obtain a brown gel;

[0022] Step 2: Dry the brown gel in a vacuum drying oven at 105-125°C for 10-12 hours to obtain a solid material, and grind it into powder;

[0023] Step 3: Place the powder into a muffle furnace and sinter at high temperature to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles are sieved to obtain particles with a size of 0.1-0.4 μm for later use.

[0024] Preferably, the specific process parameters of the high temperature sintering include: heating to 400-450°C at a heating rate of 10-12°C / min and keeping warm for 4-6h, then heating to 850-1050°C at a heating rate of 8-10°C / min and keeping warm for 10-14h.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The modified lithium-rich manganese-based lithium-ion battery positive electrode material and preparation method can provide an inert protective film layer for the positive electrode material through the provided coating layer, and can slow down the capacity decay problem caused by electrolyte corrosion and increased interface resistance during the charge and discharge cycle, which is beneficial to maintaining the overall structural integrity of the positive electrode material;

[0027] At the same time, the conductive layer provides a conductor structure, which can improve the conductivity of lithium ions and electrons, increase its first cycle specific capacity, and obtain better electrochemical performance overall;

[0028] The conductive layer and the coating layer cooperate with each other to slow down the capacity attenuation loss, while improving its specific capacity and improving its cycle endurance. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:

[0030] Figure 1 The present invention is a flow chart of the method for preparing the positive electrode material. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. In the absence of conflict, the embodiments in this application and the features in the embodiments can be combined with each other. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.

[0032] See also Figure 1The present invention describes the above technical solution in detail through the following embodiments:

[0033] Embodiment 1: A modified lithium-rich manganese-based lithium-ion battery positive electrode material, comprising a chemical formula specifically Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles, the surface of the positive electrode particles is provided with a conductive layer and a coating layer in sequence from the inside to the outside; in this embodiment, the conductive layer is made of Li 0.33 La 0.557 Ti 0.7 Cr 0.3 O3. The coating layer adopts a composite material of aluminum oxide and gallium oxide. In order to obtain a good coating structure, the coating amount of the conductive layer in this embodiment accounts for 2% of the mass of the positive electrode particles, while the coating amount of the coating layer accounts for 1% of the mass of the positive electrode particles.

[0034] In this embodiment, the raw materials of the composite material of aluminum oxide and gallium oxide include aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio of 1:0.5.

[0035] Specifically, the raw materials are chromium sulfate hexahydrate with CAS number 10101-53-8 and titanium sulfate with CAS number 13693-11-3 sold by Shanghai McLean Biochemical Technology Co., Ltd.; lithium hydroxide with CAS number 1310-66-3, lanthanum nitrate hexahydrate with CAS number 10277-43-7, and hydrated gallium nitrate with CAS number 69365-72-6 sold by Shanghai Haohong Biomedical Technology Co., Ltd.; aluminum nitrate nonahydrate with CAS number 7784-27-2 sold by Hefei Tianjian Chemical Co., Ltd.

[0036] The preparation method of the modified lithium-rich manganese-based lithium-ion battery positive electrode material in this embodiment comprises the following specific steps:

[0037] Step 1: Preparation of Li by sol-gel method 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles, first weigh 1.75 parts of LiNO3, 0.77 parts of Ni(NO3)2·6H2O, 0.77 parts of Co(NO3)2·6H2O, 2.67 parts of Mn(CHCOO)2·4H2O, 10.34 parts of monohydrated citric acid, and 1 part of polyvinyl pyrrolidone by mass, mix to obtain one unit of raw material component, dissolve the unit raw material component in 25 ml of ethylene glycol, stir at 80°C for 10 hours to obtain a brown gel; dry the brown gel in a vacuum drying oven at 115°C for 12 hours to obtain a solid material, grind it into powder, put it into a muffle furnace, and sinter it at high temperature to obtain Li 1.2 Ni 0.13 Co 0.13 Mn0.54 O2 positive electrode particles are sieved and the powder with a particle size of 0.1-0.4μm is retained for use; the high-temperature sintering parameters are controlled as follows: the temperature is raised to 450℃ and kept for 4h at a heating rate of 10℃ / min, then the temperature is raised to 950℃ at a heating rate of 8℃ / min, kept for sintering for 12h, and naturally cooled to room temperature;

[0038] Step 2: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 cathode particles are mixed into deionized water to obtain a suspension;

[0039] Step 3: Weigh 11.76 parts of chromium sulfate hexahydrate, 24.12 parts of lanthanum nitrate hexahydrate, and 16.8 parts of titanium sulfate respectively, dissolve them in deionized water to obtain a solution, mix them with the suspension, add 30 parts of lithium hydroxide, stir for 10 minutes, and then filter and dry;

[0040] Step 4: 700°C, keep warm for 4 hours, and sieve out the positive electrode particles coated with the conductive layer with a particle size less than 0.5 μm;

[0041] Step 5: Mix aluminum nitrate nonahydrate and hydrated gallium nitrate, add to anhydrous ethanol and ultrasonicate for 1 hour, add the positive electrode particles coated with the conductive layer, and stir at room temperature for 2 hours;

[0042] Step 6: Heat in a water bath at 80°C with stirring until the anhydrous ethanol is evaporated to dryness, and then place the mixture in a muffle furnace and calcine at 600°C for 6 hours to obtain positive electrode particles coated with aluminum oxide and gallium oxide.

[0043] The coating technology used in this application can form a coating Li on the outer surface of the positive electrode particles. 1.2 Ni 0.13 Co 0.13 Mn 0.54 The coating structure of O2, the main purpose of which is to form a protective film layer to improve electrochemical performance defects such as capacity attenuation and charge and discharge cycles.

[0044] It is important to explain that the inner structure Li 0.33 La 0.557 Ti 0.7 Cr 0.3 O3 is used as a conductive layer. Considering its material properties, it belongs to an ion-electron conductor and has good ion and electron conductivity. That is, the purpose of designing this structure is to improve its electrochemical performance, so as to maintain a good cycle specific capacity retention rate, so that it can ensure the smooth conduction of lithium ions and electrons during the charge and discharge cycle, improve the transmission characteristics of the positive electrode material, and help improve the performance of the battery.

[0045] The oxide used in the outer coating layer is to prevent HF produced by the decomposition of the electrolyte during the cycle from corroding the positive electrode material. Its purpose is to maintain the integrity of the material structure, reduce the problem of increased interface resistance caused by corrosion, and then slow down the decay of the cycle specific capacity. Aluminum oxide and gallium oxide, as stable inert materials, can form an effective and dense protective film layer. Limiting its thickness can avoid affecting the effect of the inner layer structure. The mutual cooperation of the inner and outer layer structures can avoid reducing the decay of the cycle specific capacity while improving its own electrochemical performance. The purpose of the mutual cooperation between the two is to obtain the effect of gap filling and enhancement.

[0046] Example 2: The only difference between this example and Example 1 is that the coating amount of the conductive layer in this example accounts for 1% of the mass of the positive electrode particles, and other conditions are the same.

[0047] Example 3: The only difference between this example and Example 1 is that the coating amount of the coating layer in this example accounts for 0.5% of the mass of the positive electrode particles, and other conditions are the same.

[0048] Example 4: The only difference between this example and Example 1 is that in this example, aluminum nitrate nonahydrate and hydrated gallium nitrate are used in a molar ratio of 1:0.2, and other conditions are the same.

[0049] Example 5: The only difference between this example and Example 1 is that in this example, aluminum nitrate nonahydrate and hydrated gallium nitrate are used in a molar ratio of 1:1, and other conditions are the same.

[0050] Comparative Example 1: The only difference between this comparative example and Example 1 is that no conductive layer is provided in this comparative example, and other conditions are the same.

[0051] Comparative Example 2: The difference between this comparative example and Example 1 is that no coating layer is provided in this comparative example, and other conditions are the same.

[0052] Comparative Example 3: The difference between this comparative example and Example 1 is that in this comparative example, only aluminum nitrate nonahydrate is used in an amount equal to the total molar amount of aluminum nitrate nonahydrate and hydrated gallium nitrate in Example 1, and hydrated gallium nitrate is not added, and other conditions are the same.

[0053] Comparative Example 4: The difference between this comparative example and Example 1 is that in this comparative example, only hydrated gallium nitrate is used in an amount equal to the total molar amount of aluminum nitrate nonahydrate and hydrated gallium nitrate in Example 1, and aluminum nitrate nonahydrate is not added, and other conditions are the same.

[0054] Comparative Example 5: The difference between this comparative example and Example 1 is that in this comparative example, only aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio of 1:2 are used, and other conditions are the same.

[0055] According to each of Examples 1-5 and Comparative Examples 1-5, battery samples were prepared; the preparation steps are as follows:

[0056] Firstly, a lithium-rich manganese-based electrode sheet was prepared. The positive electrode material sample, polytetrafluoroethylene, and conductive carbon black were mixed uniformly in a mass ratio of 8:1:1, and N-methylpyrrolidone was added to wet and grind the mixture uniformly. The mixture was then coated on a carbon-coated aluminum foil of the current collector, and vacuum dried in a vacuum drying oven at 60°C for 12 hours. The taken-out coated sheet was then cut into a circular electrode sheet with a diameter of 12 mm.

[0057] The metal lithium sheet was used as the counter electrode, Celgard2500 polypropylene organic membrane was used as the separator, and 1 mol·L -1 The ethylene carbonate and diethyl carbonate solutions of LiPF6 were used as electrolytes and assembled into a CR2025 button cell in a glove box filled with argon atmosphere;

[0058] In order to accurately evaluate the cycle performance of the battery, the Blue Electric Battery Test System was used for experimental testing. The constant current charge and discharge test method was adopted. In the test, the voltage was in the range of 2.0-4.8V, and the ambient temperature was controlled to be stable at 25℃, and the test was carried out under the condition of 1C=250mA / g.

[0059] The specific data is as follows:

[0060]

[0061] From the data in the above table, it can be seen that the data of Example 1 and Example 2 show that the coating amount of the conductive layer will affect the capacity of the first cycle ratio, and the capacity retention rate is similar; while the data of Comparative Example 1 shows obvious differences, and its first cycle capacity is greatly reduced. Although the coating layer is not changed, its capacity retention rate is also reduced;

[0062] In the data of Example 3, the first cycle specific capacity is similar, and the capacity retention rate decreases after 100 cycle specific capacity. Considering that the coating layer is less, it is considered that the dense film layer may be missing and damaged after multiple cycles. In summary, the coating amount of the conductive layer and the coating layer has an impact on the electrical performance; the coating layer is missing in the data of Comparative Example 2, but the first cycle specific capacity is similar, and the capacity retention rate is greatly reduced, indicating that the coating layer is of great significance in slowing down the decline in capacity retention rate; combined with Examples 1-2 and the data of Comparative Example 1, the conductive layer and the coating layer have mutually coordinated optimization performance, and can obtain better first cycle specific capacity and capacity retention rate, which is of great significance for the commercial performance of the battery.

[0063] From the data of Example 4, Example 5, and Comparative Example 5, it can be seen that the molar ratio of aluminum nitrate nonahydrate to hydrated gallium nitrate has an effect on the capacity retention rate. If the content of hydrated gallium nitrate is low, the capacity retention rate will be reduced. However, if the content of hydrated gallium nitrate is high, the capacity retention rate will tend to decrease. Therefore, a high ratio parameter is not used in the implementation. At the same time, combined with the data of Comparative Examples 3 and 4, it can be seen that if a single aluminum oxide or gallium oxide is used as a coating layer, the performance brought by the coating is not as good as that of composite aluminum oxide and gallium oxide. Considering that the corrosion resistance and isolation performance of the composite oxide structure is better;

[0064] In summary, it can be seen from the data that the cooperation between the conductive layer and the coating layer can obtain a positive electrode material with better performance, which is conducive to maintaining good charge and discharge cycle stability and slowing down capacity decay.

[0065] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A modified lithium-rich manganese-based lithium-ion battery positive electrode material, comprising a chemical formula specifically Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 The positive electrode particles of O2 are characterized by: The surface of the positive electrode particles is provided with a conducting layer and a coating layer in sequence from the inside to the outside; The conductive layer uses Li 0.33 La 0.557 Ti 0.7 Cr 0.3 O3; The coating layer is made of a composite material of aluminum oxide and gallium oxide.

2. The modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 1, characterized in that: The coating amount of the conductive layer accounts for 1-2% of the mass of the positive electrode particles.

3. The modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 1, characterized in that: The coating amount of the coating layer accounts for 0.5-1% of the mass of the positive electrode particles.

4. The modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 2, characterized in that: The conductive layer raw materials are chromium sulfate hexahydrate, lanthanum nitrate hexahydrate, titanium sulfate and lithium hydroxide.

5. The modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 3, characterized in that: The raw materials of the aluminum oxide and gallium oxide composite material include aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio of 1:0.2-1.

6. A method for preparing a modified lithium-rich manganese-based lithium-ion battery positive electrode material, suitable for the positive electrode material according to any one of claims 1 to 5, characterized in that: The specific steps of the preparation method of the positive electrode material are: Step 1: Preparation of Li by sol-gel method 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles are reserved; Step 2: Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 cathode particles are mixed into deionized water to obtain a suspension; Step 3: dissolving chromium sulfate hexahydrate, lanthanum nitrate hexahydrate and titanium sulfate in deionized water to obtain a solution, mixing the solution with the suspension, adding lithium hydroxide, stirring for 5-30 minutes and then filtering and drying; Step 4: 600-700°C, keep warm for 4-6 hours, and sieve out the positive electrode particles coated with the conductive layer with a particle size less than 0.5 μm; Step 5: Mix aluminum nitrate nonahydrate and hydrated gallium nitrate in a molar ratio, add to anhydrous ethanol and perform ultrasonic treatment for 0.5-1h, add the positive electrode particles coated with the conductive layer in step 4, and stir at room temperature for 1-2h; Step 6: Heat and stir in a water bath at 60-80°C until the anhydrous ethanol is evaporated to dryness, and then put it into a muffle furnace and calcine at 500-600°C for 5-6h to obtain positive electrode particles coated with aluminum oxide and gallium oxide.

7. The method for preparing the modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 6, characterized in that: The specific steps of the sol-gel method are: Step 1: Weigh 1.75 parts of LiNO3, 0.77 parts of Ni(NO3)2·6H2O, 0.77 parts of Co(NO3)2·6H2O, 2.67 parts of Mn(CHCOO)2·4H2O, 10.34 parts of citric acid monohydrate, and 1 part of polyvinylpyrrolidone, respectively, by mass, mix to obtain raw material components, dissolve the raw material components in 25 ml of ethylene glycol, stir at 70-85°C for 8-12 hours, and obtain a brown gel; Step 2: Dry the brown gel in a vacuum drying oven at 105-125°C for 10-12 hours to obtain a solid material, and grind it into powder; Step 3: Place the powder into a muffle furnace and sinter at high temperature to obtain Li 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2 positive electrode particles are sieved to obtain particles with a size of 0.1-0.4 μm for later use.

8. The method for preparing the modified lithium-rich manganese-based lithium-ion battery positive electrode material according to claim 7, characterized in that: The specific process parameters of the high temperature sintering include: heating to 400-450°C at a heating rate of 10-12°C / min and keeping the temperature for 4-6 hours, then heating to 850-1050°C at a heating rate of 8-10°C / min and keeping the temperature for 10-14 hours.

Citation Information

Patent Citations

  • Al2O3-ZrO2 coated lithium-rich manganese-based positive electrode material and preparation method thereof

    CN114229921A

  • Lithium-rich manganese-based positive electrode material with multi-layer composite structure and preparation method of lithium-rich manganese-based positive electrode material

    CN117199300A